Total Quality Management and Institutional Effectiveness: A Survey of Private Colleges of Education in Kwara State, Nigeria - Abdulganiyu Adebayo Tijani; Martins Olanrewaju Atunde; Johnson Abiodun Medupin; Jamiu Wankasi Abdulraheem; Ijeoma Charity Ogbudinkpa; Adenike Felicia Oyedele (IJER (Indonesian Journal of Educational Research), 2023)
This quantitative study inquired into the association between total quality management and institutional effectiveness of private colleges of education in Kwara State, Nigeria. The study was explanatory and correlational in nature. A sample of 736 study participants was sampled with multi-stage sampling procedure. Validated and trial tested instrument (r = .856) titled: “Total Quality Management and Institutional Effectiveness Questionnaire Index” (TQMIEQI) was used for data collection. Mean scores and linear regression analysis were appropriately applied in analyzing the three research questions raised for the study. Findings revealed that private COEDs practiced TQM to a moderate extent (CM = 3.02), while their level of effectiveness was also moderate (CM = 3.15). Findings further proved that, TQM sub-scales of quality organizational development (β = .380, P <0.05), internal-external appraisal (β = .358, P <0.05) and student-oriented focus (β = .338, P <0.05) were positively related to IE, even as quality-orientated leadership (β = -.081, P <0.05) had significant but negative correlation with IE. The study concluded that, if private COEDs aspire to attain high level effectiveness, all the four studied TQM sib-scales must be highly adopted and practiced.